PRIVATE OWNERSHIP IN OUTER SPACE – STILL WAITING? - Mijović, Milan (Pravni zapisi, 2016)
Having in mind that property rights, such as ownership right and right of use, are not regulated in detail by Space law legislation, one has to raise a question - can we regulate property rights outside Earth. At the very beginning, I will express my personal stand on Space law in general, its development and place among other legal branches. I will try to state certain impressions, which I believe, should be addressed properly. My paper shall revisit the basic principles of property law; what is an ownership, how does one acquire it or transfer it to another individual. One of the issues shall relate to a question can we simply copy-paste property laws applicable to Earth into the Space. Other theoretical questions will be dealt in my paper, including but not limited to: if the humans cannot have properties in Space, can we claim the Earth? Why would different laws apply on Earth and in Space? Or maybe one should emphasize this difference between Earth law and Space law? In addition to this, I will present two theories regarding mentioned problem. Further on, does one has to redefine the institutes of property law, including, inter alia, division into movables and immovables, having in mind the different conditions on Earth and in Space, such as gravity. With regard to breathable air being used in Space, can we charge the same, having in mind the respective costs? Fast development in Space technology, e.g. space mining will ultimately bring this issue to the table. And it has already begun. Numerous articles and announcement by space capable countries and companies, announcing plans to undergo these missions. The race has begun; not an arms race, but the race to establish more defined legal framework outside the Earth. Also, the technology is here, but the question is raised: can we, in legal sense, keep up?